Pleural empyema caused by Salmonella enteritidis in a patient with non-Hodgkin lymphoma - Kojić, Miroslav M; Nožić, Darko; Tarabar, Olivera; Perišić, Nenad (Vojnosanitetski pregled, 2017)
Introduction. Extraintestinal manifestations of nontyphoidal salmonellosis are usually seen in patients with cellular immunodeficiency. Pleural empyema caused by nontyphoidal Salmonella is very rare clinical presentation of salmonellosis and there are just a few cases described in a literature. We presented a very rare case of pleural empyema caused by Salmonella enteritidis in a patient with non-Hodgkin limphoma. Case report. A 60-year-old male with low grade B-cell lymphoma, mucosa associated lymphoid tissue (MALT) type in IV clinical degree, manifested with infiltration of stomach, bronchus, pleura and peritoneum was admitted to the hospital. Initially the patient was presented with non-specific symptoms and signs, suggesting poor general condition. During the hospitalization his pleural fluid became purulent and changes in blood counts were registered with the increase of leukocytes, especially neutrophils. A large number of leukocytes was found by microscopic evaluation of pleural fluid and Salmonella enteritidis was isolated by its culture. There were no pathogenic bacteria in stool culture and hemoculture remained sterile. Toxins A and B of Clostridium difficile were not detected in stool. The patient was treated by ciprofloxacin and cefrtiaxone for 14 days with drainage of the purulent content, what was followed by the resolution and organization of the pleural fluid. After the stabilization of his general condition, chemotherapy with cyclophosphamide, vincristine, prednisone (COP) was introduced, with complete response. Conclusion. Although rare, pleural empyema caused by nontyphoidal Salmonella should be considered in patients with severe immunosuppression, because appropriate antimicrobial therapy with surgical measures are very important for the outcome in these patients.